Associations between the presence of specific antibodies to the West Nile Virus infection and candidate genes in Romanian horses from the Danube delta - Stejskalova, K; Janova, E; Horecky, C; Horecka, E; Vaclavek, P; Hubalek, Z; Relling, K; Cvanova, M; D'Amico, G; Mihalca, A D; Modry, D; Knoll, A; et al. (Molecular biology reports, 2019)
The West Nile virus (WNV) is a mosquito-borne flavivirus causing meningoencephalitis in humans and animals. Due to their particular susceptibility to WNV infection, horses serve as a sentinel species. In a population of Romanian semi-feral horses living in the Danube delta region, we have analyzed the distribution of candidate polymorphic genetic markers between anti WNV-IgG seropositive and seronegative horses. Thirty-six SNPs located in 28 immunity-related genes and 26 microsatellites located in the MHC and LY49 complex genomic regions were genotyped in 57 seropositive and 32 seronegative horses. The most significant association (pcorr < 0.0002) was found for genotypes composed of markers of the SLC11A1 and TLR4 genes. Markers of five other candidate genes (ADAM17, CXCR3, IL12A, MAVS, TNFA), along with 5 MHC class I and LY49-linked microsatellites were also associated with the WNV antibody status in this model horse population. The OAS1 gene, previously associated with WNV-induced clinical disease, was not associated with the presence of anti-WNV antibodies.
Keywords: sentinelové organismy; Polymorphism, Single Nucleotide; Polymorphism, Restriction Fragment Length; West Nile Fever; Sentinel Species; West Nile virus; západonilská horečka; Polymorphism; Microsatellite Repeats; Horses; jednonukleotidový polymorfismus; ELISA; virus západního Nilu; SLC11A1; koně; zvířata; Microsatellite; MHC; Rumunsko; Enzyme-Linked Immunosorbent Assay; Restriction fragment length polymorphism; Romania; NKR; mikrosatelitní repetice; protilátky virové; Antibodies, Viral; TLR4; Animals; polymorfismus délky restrikčních fragmentů; Horse